Literature Review: Hubungan Asupan Makanan Siap Saji dengan Kegemukan pada Remaja - Dhea Sukma Kirana; Bambang Wirjatmadi (Media Gizi Kesmas, 2023)
Background: Overweight in adolescents has been increasing in its prevalence every year. In 2013 the incidence of overweight was 7.3% and increased to 9.5% in 2018. The impact of being overweight on adolescents is the existence of degenerative diseases and psychological problems in adolescents, such as being ostracized from their environment because of their body shape. In tackling the overweight, WHO has created a global campaign to raise awareness of all parties from policymakers to the public to minimize the occurrence of overweight in adolescents. Indonesia has made a program to prevent and control overweight, but this program is considered ineffective because the incidence of overweight in adolescents is still increasing annually. A factor causes overweight in adolescents is high consumption of fast food. Objectives: This article was made to know whether there is a correlation of fast food intake and the incidence of adolescents overweight. Methods: Article was made as a literature review from two databases, namely Google Scholar and PubMed which had been published in the last 10 years, both national and international articles. Obtained as many as 14 articles regarding the correlation of fast food intake to overweight adolescents. Discussion: Several articles have been reviewed showing that fast food consumption is associated with an increase in Body Mass Index (BMI). The adolescents who consume fast food more often have a greater risk of being overweight than adolescents who rarely consume fast food. Types of modern fast food is the type of fast food that is most often consumed. Conclusions: Can be concluded that fast food consumption had correlation with overweight in adolescents.